Acne: Pathophysiology and Management - Elvira - (PT. Kalbe Farma Tbk., 2019)
Acne is a common multifactorial inflammatory condition of the pilosebaceous follicle. Topical therapy is the first-line therapy with adjunct systemic therapy if results are unsatisfactory. Oral antibiotic, oral contraception pill or isotretinoin are indicated for inflammatory acne. Since the use topical and systemic treatments might be limited in some patients, several laser and other light sources have been developed to treat acne by decreasing the level of P. acnes or decreasing the function of the sebaceous unit. This article reviews the management strategy of acne.Acne merupakan kondisi inflamasi multifaktorial dari folikel polisebaseus. Kalsifikasi acne berdasarkan derajat keparahan ringan, sedang dan berat. Terapi topikal menjadi pilihan utama dengan tambahan terapi sistemik bila hasil belum maksimal. Terapi topikal satu jenis obat dan kombinasi seperti benzoyl peroxide, antibiotik dan retinoid telah dijual bebas. Antibiotik oral, pil kontrasespi atau isotretinoin diindikasikan unutk acne yang disertai inflamasi. Karena beberapa pasien tidak toleran dengan terapi topikal dan sistemik, terapi cahaya dan laser dikembangkan untuk menurunkan jumlah P. acnes dan menurunkan fungsi kelenjar sebaseus. Artikel ini membahas strategi penanganan acne.